Analysis of relapses in children with acute lymphoblastic leukaemia - Badowska, Wanda (Contemporary Oncology/Współczesna Onkologia, 2008)
Leukaemia is the most frequent malignant disease in childhood. It constitutes about 30-35% of all cancers under the age of 18 years. The aim of the study: was the analysis of therapy failure in children with lymphoblastic leukaemia (ALL) in the Voivodship Specialist Children’s Hospital in Olsztyn. Material and methods: : A total of 113 children aged 1.1-17.8 years (median age 5.5 years) were diagnosed with ALL between 1991 and 2007. Children were treated with six consecutive protocols accepted by the Polish Paediatric Leukaemia and Lymphoma Study Group. Analysis of therapy failure included non-responsiveness to therapy, relapse or death in remission from any cause. Results: : Adverse events occurred in 24 (21%) children, including 15 (13%) cases of relapses (2 girls and 13 boys), 5 children had early deaths as a result of toxicity or severe infections during the induction chemotherapy, 3 children had late deaths in first remission (2 girls and 1 boy); in 1 case the parents refused to continue chemotherapy. Boys were at higher risk of adverse events (relative risk RR=4.6; 95% CI 1.72-12.5; p=0.003), mostly because of relapses and infections. The probability of overall survival was 0.74±0.05; probability of event-free survival was 0.72±0.05 and probability of relapse-free survival was 0.81±0.05 of all 113 study patients. The overall survival in children with relapse was 0.14±0.09 in 15-year follow-up. Conclusions: : The most common cause of therapy failure in childhood ALL was relapse. In spite of very good outcome of children with ALL de novo, the results of therapy in children with relapsed ALL were unsatisfactory in comparison with the international study groups.